2000
DOI: 10.2165/00003088-200038030-00003
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pharmacokinetics and Pharmacodynamics of Celecoxib

Abstract: Celecoxib, a nonsteroidal anti-inflammatory drug (NSAID), is the first specific inhibitor of cyclo-oxygenase-2 (COX-2) approved to treat patients with rheumatism and osteoarthritis. Preliminary data suggest that celecoxib also has analgesic and anticancer properties. The selective inhibition of COX-2 is thought to lead to a reduction in the unwanted effects of NSAIDs. Upper gastrointestinal complication rates in clinical trials are significantly lower for celecoxib than for traditional nonselective NSAIDs (e.g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
259
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 385 publications
(270 citation statements)
references
References 43 publications
9
259
0
2
Order By: Relevance
“…The increased seizure intensity and FJB staining was associated with plasma celecoxib concentrations of 13.4 ± 2.6 μg/ml and 18.2 ± 5.8 μg/ml in mice receiving 3000 or 6000 ppm celecoxib in the diet, respectively. These plasma concentrations are within the same order of magnitude of steady state concentrations (2-3 μg/ml) observed in humans exposed chronically to 400-800 mg of celecoxib, doses normally used for the treatment of conditions such as rheumatoid arthritis and familial adenomatous polyposis [13]. Since only the unbound concentration (approximately 98%) of celecoxib is free to distribute across the blood brain barrier [14], this would place the range of brain concentrations of celecoxib in the human population and our study at approximately 160-940 nM, well above the IC 50 (39nM) of celecoxib for COX-2 [19].…”
Section: Long-term Pretreatment Of Mice With Celecoxib Increases Kainsupporting
confidence: 63%
See 1 more Smart Citation
“…The increased seizure intensity and FJB staining was associated with plasma celecoxib concentrations of 13.4 ± 2.6 μg/ml and 18.2 ± 5.8 μg/ml in mice receiving 3000 or 6000 ppm celecoxib in the diet, respectively. These plasma concentrations are within the same order of magnitude of steady state concentrations (2-3 μg/ml) observed in humans exposed chronically to 400-800 mg of celecoxib, doses normally used for the treatment of conditions such as rheumatoid arthritis and familial adenomatous polyposis [13]. Since only the unbound concentration (approximately 98%) of celecoxib is free to distribute across the blood brain barrier [14], this would place the range of brain concentrations of celecoxib in the human population and our study at approximately 160-940 nM, well above the IC 50 (39nM) of celecoxib for COX-2 [19].…”
Section: Long-term Pretreatment Of Mice With Celecoxib Increases Kainsupporting
confidence: 63%
“…For celecoxib pretreatment, PTGS-2 +/+ mice were given free access for six weeks to a diet containing 0, 3000 or 6000 ppm celecoxib. Celecoxib is a COX-2 specific inhibitor with a selectivity ratio of >375 [13]. Celebrex™ capsules (400 mg; Pfizer Inc, New York, NY) were obtained from the NIH Division of Veterinary Medicine and were incorporated into feed by Research Diets, Inc. (New Brunswick, NJ) [73].…”
Section: Animal Housingmentioning
confidence: 99%
“…Celecoxib is a potent selective COX-2 inhibitor used in the treatment of rheumatoid and ostheoarthritis [3]. Celecoxib is metabolized in the liver by methyl hydroxylation, followed by further oxidation to carboxycelecoxib, which is the major metabolite found in blood.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of fentanyl and celecoxib maintained a low postoperative pain score, the effect being almost comparable to that of epidural anesthesia, except on POD 1. Moreover, the need for rescue analgesic drugs was significantly lower in group FC than in group E. In a previous report, the mean maximum drug plasma concentration of celecoxib was reached about 2-4 h after a single 200-mg oral dose [24]. Because NSAIDs exert synergistic analgesic effects when used concomitantly with opioids [20], we considered that the continuous fentanyl infusion should be stopped when the blood concentration of celecoxib had reached the therapeutic dose.…”
Section: Discussionmentioning
confidence: 94%
“…It has been suggested that NSAIDs might increase the risk of gastrointestinal ulcers, renal toxicity, or anastomotic leakage [24,28]. Although celecoxib, a selective COX-2 inhibitor, has renal toxicity equivalent to that of a non-selective COX inhibitor, it has less gastrointestinal toxicity [24].…”
Section: Discussionmentioning
confidence: 99%